2019
DOI: 10.5468/ogs.2019.62.6.429
|View full text |Cite
|
Sign up to set email alerts
|

ICSI using fresh and frozen PESA-TESA spermatozoa to examine assisted reproductive outcome retrospectively

Abstract: ObjectiveThe male reproductive system generates, accumulates, and transports the sperm. In this study, 2 methods of surgically retrieving sperm, namely, testicular sperm aspiration (TESA) and percutaneous epididymal sperm aspiration (PESA), are discussed and studied in men aged ≤38 years to achieve successful conception using assisted reproductive technology. The purpose was to assess the fertilization rate (FA), clinical pregnancy, and live birth rate (LBR) with sperm.MethodsA total of 287 semen samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…But analogous with the results of our study, most studies have suggested a similar results in terms of fertilization rate, cleavage rate and clinical pregnancy rate in ICSI with frozen testicular sperm [12][13][14]. OU L et al [12] found that frozen testicular sperm or fresh testicular sperm extracted from patients with OA have the same 2PN fertilization and pregnancy potential (74.41% vs 76.43% and 46.81% vs 53.39%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…But analogous with the results of our study, most studies have suggested a similar results in terms of fertilization rate, cleavage rate and clinical pregnancy rate in ICSI with frozen testicular sperm [12][13][14]. OU L et al [12] found that frozen testicular sperm or fresh testicular sperm extracted from patients with OA have the same 2PN fertilization and pregnancy potential (74.41% vs 76.43% and 46.81% vs 53.39%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…After the screening of inclusion and exclusion criteria, 20 articles were obtained to meet the requirements (Fig. 1) [7,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The main characteristics and NOS scores of each article included in this study were shown (Table 1 and Supplementary Table S1).…”
Section: Study Selection Process and Characteristics Of The Included Studiesmentioning
confidence: 99%
“…During ICSI cycles using epididymal or testicular sperm, cryopreservation of retrieved sperm during diagnostic procedure for ICSI has shown to be valid option to avoid repeating puncture or biopsy. While earlier studies suggested that cycles using frozen-thawed retrieved sperm resulted in comparable pregnancy outcomes than those using fresh retrieved sperm [4,5], recent evidence suggested a lower pregnancy rate by using frozen epididymal/testicular sperm compared with fresh epididymal/testicular sperm [6,7], suggesting a potential effect of cryopreservation on injected sperm. Cryopreservation may lead to genetic and epigenetic changes in spermatozoa [8], which affect not only implantation of the transferred embryo but also neonatal outcomes of the offspring.…”
Section: Introductionmentioning
confidence: 96%